Effectiveness Test of Anthelmintic Ethanol Extract of The Perwinkle Stem (Chatarantus roseus) Plant on Roundworms (Ascaris lumbricoides) (International Forum of Researchers and Lecturers, 2024)
Worms are an infectious disease caused by parasites in the form of ringworm (Ascaris Lumbricoides). The purpose of this study is to determine the anthelmintic power of ethanol extract of virgin stem (Catharanthus roseus (L) G.Don) on the mortality of roundworms (Ascaris lumbricoides). The stages of the study include sample sorting, extraction, phytochemical screening, and anthelmintic activity tests. Extract preparations are made in concentrations of 5%, 10%, and 15%. For positive control, pirantel pamoate (Combantrin) is used as much as 10 ml while for negative control 0.9% NaCl is used as much as 25 ml. Soaked with various treatments in petri dishes. Observations are made every 1 hour for 5 hours to see if the roundworms are alive or dead. The test animals used were 10 roundworms. The anthelmintic activity test was carried out by soaking worms in concentrations of 5%, 10%, and 15%, respectively The results of this study showed that the extract of virgin stem (Catharanthus roseus (L) G.Don) had an anthelmintic effect on roundworms . The higher the concentration of the extract, the higher the anthelmintic power. In the extract concentration of 15% has almost the same anthelmintic ability as (Combantrin).